2003
DOI: 10.1177/039139880302601205
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Biomaterial Compatibility: In Vivo Tissue Response versus in Vitro Cell Behavior

Abstract: Biocompatibility relies essentially on surface phenomena, represented by cell-cell, cell-material and material (polymer)-protein interactions. An in vivo and in vitro experimental investigation was carried out on the biomaterials of two different classes with a good potential for in situ utilisation. Non-resorbable (Polypyrrole, Polyaniline, Polyimide) and resorbable (PLLA-PDXO-PLLA) materials for tissue engineering were studied for their overall tissue tolerance and cellular interactions. These non-resorbable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(69 citation statements)
references
References 32 publications
0
63
0
Order By: Relevance
“…This potential difference is maintained at a steady level when excitable cells are inactive and is called the resting potential (Paul, 1975). Regarding the electrical properties of cells, electrical signals strongly affect cell behaviour, affecting ion influx across the cell membrane, altering the membrane potential and conditioning the intracellular signal transduction pathways (Mattioli-Belmonte et al, 2003). The transition of information from one place to another in the nervous system takes place along the axon.…”
Section: Electrical Properties Of Nerve Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This potential difference is maintained at a steady level when excitable cells are inactive and is called the resting potential (Paul, 1975). Regarding the electrical properties of cells, electrical signals strongly affect cell behaviour, affecting ion influx across the cell membrane, altering the membrane potential and conditioning the intracellular signal transduction pathways (Mattioli-Belmonte et al, 2003). The transition of information from one place to another in the nervous system takes place along the axon.…”
Section: Electrical Properties Of Nerve Cellsmentioning
confidence: 99%
“…However, recently there has been more evidence of the ability of PANI and PANI variants to support cell growth (Mattioli-Belmonte et al, 2003). Wang et al (1999) investigated the in vivo tissue response to PANI and found no characteristic features resulting from tissue incompatibility after PANI implantation.…”
Section: Polyanilinementioning
confidence: 99%
“…We found cell viability to be high when exposed to low concentrations (0.2 mg Á mL À1 ) of CPs and to decrease above 1.5 mg Á mL À1 (a concentration greater than the mass in the individual foams), yet the CPs are markedly less toxic than nanoparticles composed of polypyrrole alone, [25] or indeed poly(3-thiophene acetic acid). [9] Silk-based materials are relatively non-immunogenic in vivo, with inflammatory responses in rats typically lower than collagen or polylactic acid, [26] as is also true of polyaniline [27] and polypyrrole [27] derivatives. Hence, we conclude that, while imperfect, such CPs represent valuable lead structures for the future development of conductive biomaterials.…”
Section: Preparation and Characterization Of Scaffoldsmentioning
confidence: 99%
“…PAni has been previously explored in several biomedical applications including biosensors and scaffolds in tissue engineering, and demonstrates biocompatibility in both in vitro and in vivo analysis. [17,19,20] Here, our primary objectives were to investigate cell response to nanofibrous substrates prepared from the mixture of PLCL and PAni using camphorsulfonic acid (CPSA) as the dopant. First, the effect of incorporated PAni on the morphology, mechanical strength, surface characteristics, and conductivity of the fabricated nanofibers was examined.…”
Section: Introductionmentioning
confidence: 99%